2021
DOI: 10.1249/mss.0000000000002628
|View full text |Cite
|
Sign up to set email alerts
|

Sex Dimorphism in Muscle Damage–induced Inflammation

Abstract: Introduction:The purpose of this study was to determine the effect of resistance exercise (RE)-induced hormonal changes on intramuscular cytokine gene expression after muscle damage in untrained men and women. Methods: Men (n = 8, 22 ± 3 yr) and women (n = 8, 19 ± 1 yr) completed two sessions of 80 unilateral maximal eccentric knee extensions followed by either an upper body RE bout (EX) or a time-matched period (CON). Muscle samples (vastus laterals) were analyzed for mRNA expression of interleukin (IL) 6, IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 44 publications
2
23
1
Order By: Relevance
“…Since autophagy is critical to tag and to engulf damaged protein for degradation, the different autophagy responses between sexes could be due to a greater demand for degrading damaged protein in men. In accordance, we had previously reported that with the same relative total work performed, CK was greater for men than women at 12 h and with a similar trend at 24 h (Luk et al, 2021). The degree of muscle damage might, at least partly, explain the increase in autophagosome degradation observed in men but not in women at 24 h. With the importance of autophagy in muscle regeneration, the lack of change in autophagy for women could be interpreted to negatively impact muscle recovery.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Since autophagy is critical to tag and to engulf damaged protein for degradation, the different autophagy responses between sexes could be due to a greater demand for degrading damaged protein in men. In accordance, we had previously reported that with the same relative total work performed, CK was greater for men than women at 12 h and with a similar trend at 24 h (Luk et al, 2021). The degree of muscle damage might, at least partly, explain the increase in autophagosome degradation observed in men but not in women at 24 h. With the importance of autophagy in muscle regeneration, the lack of change in autophagy for women could be interpreted to negatively impact muscle recovery.…”
Section: Discussionsupporting
confidence: 92%
“…To confirm muscle damage, serum creatine kinase (CK) activity was measured immediately after the maximal effort unilateral eccentric knee extension exercise (IMD; CK is not expected to differ from baseline at this time point) and at 12 h and 24 h after completion of the upper body RE or 20 min rest. The CK results have been reported previously ( Luk et al, 2021 ). Briefly, CK was significantly greater (1.6-fold) at 12 h in men than women.…”
Section: Methodssupporting
confidence: 87%
See 3 more Smart Citations